Soil chemical characteristics and phosphatase activity in soil of two mangosteen cultivation patterns in the mangosteen thematic village, District of pauh, Padang - Agustian; Dwipa, Indra; Yunita, Roza; Ninda Rosadi, Firsta; Dwi Putri, Kesi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2025)
This research discusses the critical role of phosphatase enzymes in soil, particularly in the phosphorus cycle and soil fertility. Acid and alkaline phosphatases are identified as crucial components, with their activities serving as indicators of soil fertility. This study evaluates the soil chemical and biological characteristics in mangosteen orchards in the Mangosteen Thematic Village, specifically in monoculture and polyculture cultivation patterns on slopes ranging from 8-15%. Soil pH, organic C, available P, total P, soil respiration, microbial C-biomass, and phosphatase enzyme activities were assessed at 0-20 cm and 20-40 cm depths. Total P did not show significant changes based on cultivation patterns. The results show that the soil pH values tend to be acidic to slightly acidic (5.21- 5.45) with no significant differences based on depth. Organic C, available P, soil respiration, microbial C-biomass, and acid phosphatase enzyme activity were higher in polyculture cultivation patterns but alkaline phosphatase enzyme activity was higher in monoculture. The cultivation pattern influences the dynamics of agricultural ecosystems and should be considered in land management to enhance productivity and soil ecosystem balance.